DYNAMIC COMMUNICATION : 27 STRATEGIES TO GROW, LEAD & MANAGE YOUR BUSINESS - Schiefelbein, Jill
This book contains 27 actionable strategies that readers can use to demonstrate dynamic communication and their organization to drive results. While the chapters and strategies are organized intentionally each one is designed to be accesed individual